Adaptation and Validation of a Portuguese Version of the Sports Motivation Scale-II (SMS-II-P) Showing Invariance for Gender and Sport Type - Rodrigues, Filipe (2021)
In the present cross-sectional study, we adapted and examined the validity of a Portuguese version of the Sport Motivation Scale II (SMS-II-P) within a sample of 1148 Portuguese athletes (women ¼ 546, men ¼ 602) with a mean age of 18.45 years (SD ¼ 5.36), participating in a variety of sports (i.e., football, basketball, swimming, and athletics). We conducted confirmatory factor analysis, convergent and discriminant validity analysis, and multigroup analysis across participants’ sport type (team and individual) and gender. We also examined the correlations between the SMS-II-P behavioral regulations and basic psychological needs satisfaction. The results supported that the SMS-II-P had good psychometric properties and was invariant across gender and sport type. The scale demonstrated good convergent and discriminant validity, and the subscales achieved adequate internal consistency. Correlations between the six types of regulation measured in the SMS-II supported the distinction between autonomous and controlled behavioral regulations, and the correlations between these subscales and other measures of autonomy, competence, and relatedness satisfaction provided evidence of the self-determination continuum. Implications of this research for assessing Portuguese athletes and conducting future research are discussed.